Pain Reduction During Dysmenorrhea With Yoga Movement - Julaecha Julaecha; Safitri Safitri; Ajeng Galuh Wuryandari (poltekkes kemenkes mataram, 2020)
Dysmenorrhea is a menstrual disorder caused by an imbalance of the hormone progesterone in the blood. The incidence of dysmenorrhea 45-95% among women of childbearing age, occurs in adolescents who lack sports. The impact of dysmenorrhea is the percentage of attendance at college and not participating in learning. One way to deal with pain is yoga. This study aims to analyze the effect of yoga on dysmenorrhea. The study design was a quasi-experimental one-group pre-post test design. The sample in this study was 33 female students. The sampling technique was purposive sampling. The instrument used to measure the scale of pain during menstruation uses the Numeric Rating Scale (NRS). The collected data tested for normality data, and the data is normal, then the statistical test is done using repeated Anova test. The analysis showed that there were differences in pain scale before and after months 1 and 2 interventions with mean (sb) pain scale (5.8 (1.6) vs. 4.0 (1.7) vs. 2.7 (1.3) and P <0.05). The study concludes that yoga affects the decrease in pain scale during dysmenorrhea.